2023
DOI: 10.3389/fnut.2023.920998
|View full text |Cite
|
Sign up to set email alerts
|

Impact of vitamin D on the prognosis after spinal cord injury: A systematic review

Abstract: Vitamin D (VitD) insufficiency is a worldwide health problem and affects billions of people. Spinal cord injury (SCI) patients seem more susceptible to developing suboptimal levels of VitD. However, the literature regarding its impact on the prognosis of SCI is limited. Thus, in this review, we systematically investigated the published studies via a combination of keywords associated with SCI and VitD in four medical databases (Medline, Embase, Scopus, and Web of Science). All included studies were analyzed, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“…patients have mixed pain; nerve root impingement is supplied by distorted neurodynamics in the course of inflammation that accompanies every degenerative process. Vitamin D receptors are found in several parts of the nervous system, indicating that PHSD has a protective role in preventing neurotoxicity and aiding in detoxification pathways due to its vitamin D content [63].…”
Section: Discussionmentioning
confidence: 99%
“…patients have mixed pain; nerve root impingement is supplied by distorted neurodynamics in the course of inflammation that accompanies every degenerative process. Vitamin D receptors are found in several parts of the nervous system, indicating that PHSD has a protective role in preventing neurotoxicity and aiding in detoxification pathways due to its vitamin D content [63].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, nutrient intake and nutrition behaviors have important implications for the management and prevention of SCI/D secondary conditions, such as pressure injuries, bowel and bladder dysfunction (Bernardi et al, 2020;Richards et al, 2004;Yeung et al, 2021), and bone health (L. Wang et al, 2023;Weaver et al, 2021). For example, after SCI/D, pressure injuries rapidly deplete the limited protein stores as the body attempts to heal the wound, which occurs in the presence of already diminished protein reserves due to reduced skeletal muscle mass in this population (Vecin & Gater, 2022).…”
Section: Impact and Implicationsmentioning
confidence: 99%
“…Also, fiber and water intake must be regulated for individuals with SCI/ D and neurogenic bowel dysfunction due to potentially reduced gastrointestinal emptying and motility (Bernardi et al, 2020;Holmes & Blanke, 2019;Kurze et al, 2022;Yeung et al, 2021). Further, in persons with SCI/D, secondary conditions of osteoporosis and fractures require tailored treatment recommendations for vitamin D, calcium, and phosphorus intake (L. Wang et al, 2023;Weaver et al, 2021). As a result, nutrient intake behaviors may need to be adjusted in the presence of SCI/D secondary conditions.…”
Section: Impact and Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with SCI are particularly vulnerable to vitamin D deficiency for various reasons, including insufficient dietary intake, the use of anticonvulsant medications, and limited sunlight exposure [ 131 ]. A meta-analysis involving 13 studies with 1,962 patients revealed a high prevalence of vitamin D insufficiency (81.6%) and deficiency (52.5%) in the SCI population [ 115 ] ( Table 2 ). Vitamin D plays a critical role in maintaining skeletal health, muscle function, and immune system efficiency.…”
Section: Vitamin D and Scimentioning
confidence: 99%